2009
DOI: 10.1182/blood-2009-02-203604
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI contributes to thrombin generation in the absence of factor XII

Abstract: During surface-initiated blood coagulation in vitro, activated factor XII (fXIIa) converts factor XI (fXI) to fXIa. Whereas fXI deficiency is associated with a hemorrhagic disorder, factor XII deficiency is not, suggesting that fXI can be activated by other mechanisms in vivo. Thrombin activates fXI, and several studies suggest that fXI promotes coagulation independent of fXII. However, a recent study failed to find evidence for fXII-independent activation of fXI in plasma. Using plasma in which fXII is either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
152
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(164 citation statements)
references
References 46 publications
8
152
1
3
Order By: Relevance
“…It was demonstrated that the activation of FXI by thrombin mediates the propagation of the coagulation reaction in plasma (7,8,13). We investigated whether FV(a) contributes to this mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the activation of FXI by thrombin mediates the propagation of the coagulation reaction in plasma (7,8,13). We investigated whether FV(a) contributes to this mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…32 Recalcifying plasma in the absence of thrombin did not induce clotting during the observation period ( Figure 3A second column from left) and had little effect on the relatively short clotting times with 1.25nM ␣-IIa ( Figure 3C). With ␣-IIa, results were not affected by antibodies that block FIX activation by FXIa (O1A6) 19 or FXI activation by FXIIa (14E11), 19,33 or by a FXIIa inhibitor (CTI), indicating any FXIa or FXIIa formed does not influence fibrin formation. rMz-IIa at 2.5nM induced clotting with recalcification, but not without it, indicating that ␣-IIa must be forming from endogenous prothrombin ( Figure 3D).…”
mentioning
confidence: 97%
“…18 FXI activation by ␣-IIa would explain the phenotypic differences between FXI and FXII deficiency. 19,20 FXI is a homolog of prekallikrein (PK), the zymogen of a protease (␣-kallikrein) involved in kinin formation. 17 Although FXI and PK are both FXIIa substrates, PK is not activated by ␣-IIa.…”
mentioning
confidence: 99%
“…3,4 Subsequent work provided a physiological basis by showing that activated platelets could sustain this reaction. 5,6 The laboratory of Dr Morrissey established the mechanism of this activation by showing that polyphosphate released from platelet-dense granules was the agent that promoted thrombin activation of factor XI.…”
mentioning
confidence: 99%
“…[4][5][6] Although impaired antimicrobial T-cell immunity posttransplant is frequently attributed to reduced T-cell recovery, competent adaptive immune responses require several steps, including T-cell activation by APCs such as dendritic cells (DCs). Moreover, there is a growing awareness that other immune cells besides ab T cells contribute to anti-CMV immunity posttransplant, and the pathophysiology of CMV reactivation involves more than just T-cell deficiency.…”
mentioning
confidence: 99%